Reflections of inequality : women and mental health - Gómez, Adriana (Latin America and Caribbean Women's Health Network SantiagoCL, 2001)
Addresses general aspects of women's mental health, the daily impact of gender roles on their psychological state, the special hazards faced at work, the tremendous impact of gender-based violence, and the burden of body image in contemporry society.